Continuous or Interrupted Suture for Hepaticojejunostomy in Pancreaticoduodenectomy (The HEKTIK Trial): Findings of a Randomized, Controlled, Single-Center Superiority Trial. - Brunner, Maximilian; Golcher, Henriette; Krautz, Christian; Kersting, Stephan; Weber, Georg; Grützmann, Robert (Deutsches Ärzteblatt international, 2024)
BACKGROUND: Over 6000 pancreaticoduodenectomies are per - formed each year in Germany, and hepaticojejunostomy is a crucial step of the procedure. An anastomotic leak of hepaticojejunostomy can cause major postoperative complications. The aim of this trial was to compare the morbidity and efficiency of continuous versus interrupted suturing for hepaticojejunostomy in pancreaticoduo - denectomy. METHODS: In a randomized, controlled, single-center trial (German Clinical Trials Register No. DRKS00024395), patients scheduled for elective open partial pancreaticoduodenectomy with hepaticoje - junostomy between January 2020 and May 2023 were randomly assigned in a 1:1 ratio to suturing of the hepaticojejunostomy with either a continuous or an interrupted technique. The primary endpoint was anastomotic leakage from the hepaticojejunostomy in the first three days after surgery. Further perioperative parameters were secondary endpoints, including later leakage, other complications, the duration of hepaticojejunostomy, and the cost of hepaticojejunostomy. RESULTS: The 100 patients in the trial consisted of 50 in each group. The rate of early anastomotic leakage was 2% in both groups (95% confidence interval for the difference, [-5.5%; 5.5%]; p = 1.000). As for the secondary endpoints, there were no relevant intergroup differences in any other short-term or long-term morbidity parameters. Continuous suturing of the hepaticojejunostomy was, however, 31% faster and 68% cheaper in material costs. CONCLUSION: These data imply that continuous and interrupted suturing techniques yield equally good clinical outcomes in hepaticojejunostomies of hepatic ducts with diameter 5 mm or more. Continuous suturing is, however, both faster and cheaper.
EVALuna2:583241